Livelihoods and coping strategies based on migration for families affected by environmental deteriorations in high andean communities «There’s no life here; that’s why they went away» - Cavagnoud, Robin (2020)
In Andean communities, many families whose livelihoods depend on farming and raising livestock are exposed to increasing degradation of their ecosystem and to food insecurity. The objective of this paper is to examine the extent to which families use migration strategies, based on multi residence and migratory circulation, to diversity their sources of income and mitigate the consequences of ecological degradation on their living conditions. The results are part of a socio-demographic research conducted in 2015 and 2016, which focused on domestic strategies for addressing environmental problems in a sample of 203 families living in five high Andean communities around Lake Titicaca. Most of families have migrant members and young adults between ages 20 and 35 represent the largest number of them. Nevertheless, their departure does not constitute an explicit form of adaptation to the ecological degradation. The quest for better conditions and opportunities in urban territories as well as interests related to their life stage and cycle, are the main determinants of their migration decisions. Despite the ecological problems affecting families, the desire for personal autonomy of the migrants is the main impetus for migration and there is no family organization based on multi residence and circular migration as an explicit livelihood for adaptation to environmental deterioration in rural areas.